Dyes removal from water using low cost absorbents (2017)
In this study, the removal capacity of low cost adsorbents during the adsorption of Methylene Blue (MB) and Congo Red (CR) at different concentrations (50 and 100mg•L-1) was evaluated. These adsorbents were produced from wood wastes (cedar and teak) by chemical activation (ZnCl2). Both studied materials, Activated Cedar (AC) and activated teak (AT) showed a good fit of their experimental data to the pseudo second order kinetic model and Langmuir isotherms. The maximum adsorption capacities for AC were 2000.0 and 444.4mg•g-1 for MB and CR, respectively, while for AT, maximum adsorption capacities of 1052.6 and 86.4mg•g-1 were found for MB and CR, respectively. © Published under licence by IOP Publishing Ltd.